Characterization of Pantoea species that causes leaf blight disease of rice in Peninsular Malaysia - Azizi, Mohammad Malek Faizal (2020)
Bacterial leaf blight (BLB) disease is a major constraint in rice cultivation as it reduces yield and quality of grains, hence affecting the economic development of rice production in Malaysia. The disease symptomatic phase exhibited as yellowing color and water soaking from the leaf tip, which later turned into brown stripes. This study was conducted to isolate and characterize Pantoea species (Pantoea spp.) associated with leaf blight disease of rice in Peninsular Malaysia via phenotypic and molecular approaches. Diseased plants exhibiting blight symptoms were collected from rice fields in Kedah and Selangor. Thirty isolates were characterized via phenotypic, pathogenicity test and molecular approaches. Based on the phenotypic characteristics, all isolated bacteria were Gram-negative facultative anaerobes, motile, positive catalase and KOH, indole positive, incapable of producing hydrosulfuric acid and positive for utilization of carbohyrdates. Colonies were round, smooth with irregular edges, and produced yellow pigment on nutrient agar and King’s B agar medium. Pathogenicity test revealed that Pantoea species isolates resembled blight symptoms as originally found in the rice fields, and were later confirmed as Pantoea ananatis and Pantoea stewartii subspecies indologenes using gyrB and gaIE genes amplification respectively. Statistical analysis revealed that the MR220 CL1 and MR269 rice varieties were highly susceptible to Pantoea spp., except for the PA3 isolate which was susceptible only to MR269 rice variety. Based on AUDPC result, MR220 CL1 rice variety was more susceptible towards Pantoea spp. compared to MR269 rice variety. All strains were identified based on the gyrB sequence of Pantoea spp. genome analyses. Fragment of the gyrB gene sequence was amplified with primers PANsp_gyrB-F and PANsp_gyrB-R and BLASTn analysis showed 95 to 99% identical to reference strains in the GenBank database. A phylogenetic analysis constructed using MEGA 7 software of the gyrB gene sequence displaying two clusters comprising 22 strains into P. ananatis (cluster I), and eight strains into P. stewartii (cluster II) in GenBank database with 96% and 99% bootstrap value respectively. The amplification of the gaIE gene revealed that all P. stewartii strains were confirmed as P. stewartii subspecies indologenes with 99% identical to reference strain in the Genbank database. These findings may provide insights into genetic studies and significant documentation of Pantoea spp. associated with leaf blight disease of rice in Malaysia.